The relationship between urbanization, energy consumption, economic growth, and carbon dioxide emissions in middle eastern countries: Saudi Arabia, Jordan and Egypt - Abdulaziz Aldegheishem (Environmental Research Communications, 2024)
The Middle East region is a strategic driver of the global economy. However, ensuring environmental sustainability in the context of rapid urban and economic changes remains a major challenge for most Middle Eastern countries. Although researchers have widely examined factors affecting carbon dioxide emissions (CO _2 ), little attention has been paid to the Middle Eastern countries. This study uses an ARDL model to examine the nexus between urbanization, energy consumption, economic growth, and CO _2 emissions for three Middle Eastern countries, (Saudi Arabia, Egypt and Jordan) based on panel data for the period from 1990 to 2023. Findings reveal that urbanization has had no significant impact on CO _2 emissions in Egypt; this is not in line with the findings for Saudi Arabia and Jordan, where urbanization has reduced CO _2 emissions in the long- and short-run, indicating that urban policies are well matched with environmental goals in both countries. However, empirical results indicate that energy consumption has had a positive effect on CO _2 emissions in the long- and short-run in all three countries and economic growth has also had a positive impact on CO _2 emissions. The fact that economic growth has been unable to mitigate CO _2 emissions indicates a mismatch between economic policies and environmental goals. This article suggests a series of valuable insights for policymakers to reduce CO _2 emissions.